Photodynamic Inactivation of Cariogenic Pathogens Using Curcumin as Photosensitizer - Araújo, Natália Costa; De Menezes, Rebeca Ferraz; Carneiro, Vanda Sanderana Macêdo; Dos Santos-Neto, Alexandrino Pereira; Fontana, Carla Raquel [UNESP]; Bagnato, Vanderlei Salvador; Harvey, Catherine Malinda; Gerbi, Marleny Elizabeth Martinez (SAGE Publications, 2017)
Objective: This investigation assessed the susceptibility of Streptococcus mutans and Lactobacillus acidophilus to Photodynamic Therapy (PDT) when grown simultaneously in dentine carious lesions. Background data: PDT is a technique that utilizes light to activate photosensitizers in the presence of oxygen to produce reactive radicals. Materials and methods: A culture medium of 1% glucose, 2% sucrose, 1% young primary culture of L. acidophilus 108 CFU/mL, and S. mutans 108 CFU/mL was utilized to inoculate the bacterial induced caries on human dentine slabs. Different concentrations of the photosensitizer (0.75, 1.5, 3.0, 4.0, and 5.0 g/L) were activated through exposure to the light-emitting diode source with a central wavelength of 450 nm and a fluency of 5.7 J/cm2. Two light intensities (19 and 47.5 mW/cm2) were tested. Four different groups were analyzed: L-D- (control group), L-D+ (drug group), L+D+1 (PDT group 1, light intensity of 19 mW/cm2), and L+D+2 (PDT group 2, light intensity of 47.5 mW/cm2). ANOVA/Tukey tests were utilized to compare groups (α = 5%). Results: Both light intensities required 5.0 g/L of curcumin for significant bacterial reduction (p < 0.05). No significant effect was found for L-D+, thus proving the absence of a potential inherent toxicity. Conclusions: Curcumin has a toxic effect on microorganisms at appreciable concentrations upon photoactivation. However, it was required to use the maximum concentration of the drug for a successful procedure.
Keywords: dentin; dentistry; photodynamic therapy